The isolation, characterisation and chemotaxonomic significance of secondary metabolites from selected South African Laurencia spp. Rhodophyta - Fakee, Jameel (Rhodes University, Faculty of Pharmacy, Pharmacy, 2015)
Bioprospection of marine organisms as a potential source for lead drugs is becoming increasingly popular. The secondary metabolome of these organisms consists of structurally diverse molecules possessing unprecedented carbon skeletons, the biosynthesis of which occurs via complex metabolomic pathways driven by specialist enzymes. This structural novelty is highly influential on the favourable bioactivity these compounds display. A prominent example of such a compound is trabectedin marketed as YondelisÂ®. Registered for the treatment of soft tissue sarcomas, this marine drug was developed from extracts of the tunicate Ecteinascidia turbinata. South Africa is renowned for possessing a highly diverse marine biota including several endemic species of marine red algae belonging to the Laurencia sensu stricto genus, which falls within the Laurencia complex. Despite having a good reputation for fascinating secondary metabolites, the taxonomy of Laurencia natural products is proving challenging for reasons including the presence of cryptic species, as well as individual species displaying morphological variability. The aim of this study was thus to isolate secondary metabolites from various South African Laurencia spp. and subsequently assess their chemotaxonomic significance by analysis of a parallel plastid rbcL phylogeny study of Laurencia spp. This study reports the first phycochemical investigation into Laurencia natalensis Kylin, Laurencia cf. corymbosa J.Agardh, Laurencia complanata (Suhr) Kützing, Laurencia sodwaniensis Francis, Bolton, Mattio and Anderson submitted, Laurencia multiclavata Francis, Bolton, Mattio and Anderson submitted, and a South African specimen of Laurenciella marilzae Gil-RodrÃguez, SentÃes, DÃaz-Larrea, Cassano and M.T. Fujii (basionym: Laurencia marilzae) originally described from Spain. Additionally, the chemical profiles of previously explored species Laurencia flexuosa Kützing and Laurencia glomerata Kützing were re-investigated. The organic extracts of the above species afforded 31 compounds belonging to a wide array of structural classes including halo-chamigranes, linear C15 acetogenins, indole alkaloids, cuparanes and cyclic bromo-ethers. A new tri-cyclic keto-cuparane (4.4) was isolated from L.cf. corymbosa alongside the new cuparanes 4.1 and 4.7. Algoane (5.9), a unique marker compound isolated from L. natalensis, was previously only reported from a sea-hare. Such marker compounds which are exclusive to an individual algal species increase the ease of their subsequent identification. The feasibility of chemotaxonomy as an additional tool to classify Laurencia spp. Was established as broad predictions of a specimen's phylogeny, based on representatives of its secondary metabolome, proved viable. The study specimens were shown to possess similar chemical profiles to their sister species e.g. L. complanata, L. sodwaniensis and L. multiclavata produced similar metabolites to their sister species as inferred by an rbcL phylogeny tree. Finally, a 1H NMR profiling study on the crude organic extracts of various Laurencia spp. generated distinctive, reproducible spectra, exposing the value of NMR spectroscopy as a rudimentary species discernment tool.
Keywords: Uncatalogued